Coloring of fullerenes. Issue 11 (2nd November 2018) - Bakaein, Samane; Tavakoli, Mostafa; Ashrafi, Ali Reza; Ori, Ottorino
Abstract: A ( k, 6)-fullerene graph is a planar 3-connected cubic graph whose faces are k-gons and hexagons. The aim of this paper is to compute the equitable chromatic, b-chromatic and list chromatic numbers of some fullerenes.